2022
DOI: 10.1101/2022.11.05.515306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xist ribonucleoproteins promote female sex-biased autoimmunity

Abstract: Autoimmune diseases disproportionately affect females more than males. The XX sex chromosome complement is strongly associated with susceptibility to autoimmunity. XIST long noncoding RNA (lncRNA) is expressed only in females to randomly inactivate one of the two X chromosomes to achieve gene dosage compensation. Here, we show that the XIST ribonucleoprotein (RNP) complex, comprised of numerous autoantigenic components, is an important driver of sex-biased autoimmunity. Inducible transgenic expression of a non… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 100 publications
0
9
1
Order By: Relevance
“…This result seems in apparent contradiction with observations of the present study in which reduced levels of Xist in female immune cells, associated with altered XCI, trigger spontaneous systemic autoimmunity. The study by Dou et al ( 60 ) indicates that Xist RNP itself harbors immunogenic properties upon release from dying male cells that are not naturally expressing Xist , whereas, in the present study, altered XCI is constitutive and triggers spontaneous autoimmunity in aged female mice of the non-autoimmune prone background (C57/BL6). These two findings are, however, not mutually exclusive and may reflect the wide variety of causes, manifestations, and onset of autoimmunity.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This result seems in apparent contradiction with observations of the present study in which reduced levels of Xist in female immune cells, associated with altered XCI, trigger spontaneous systemic autoimmunity. The study by Dou et al ( 60 ) indicates that Xist RNP itself harbors immunogenic properties upon release from dying male cells that are not naturally expressing Xist , whereas, in the present study, altered XCI is constitutive and triggers spontaneous autoimmunity in aged female mice of the non-autoimmune prone background (C57/BL6). These two findings are, however, not mutually exclusive and may reflect the wide variety of causes, manifestations, and onset of autoimmunity.…”
Section: Discussioncontrasting
confidence: 52%
“…Alterations of XCI as a cause of different autoimmune manifestations have not been reported so far but not thoroughly investigated either. Two independent studies have recently reported that (i) XIST levels were elevated in blood leucocytes from women with SLE ( 59 ) and that (ii) transgenic expression of Xist lncRNAs in male mice can promote autoantibodies directed against Xist RNP in the context of pristane-induced lupus in a permissive genetic background (SJL/J) ( 60 ). This result seems in apparent contradiction with observations of the present study in which reduced levels of Xist in female immune cells, associated with altered XCI, trigger spontaneous systemic autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the role of extracellular RNases in the regulation of inflammatory responses, several reports have shown that ectopic administration of extracellular RNases reduces inflammation in mouse models of Lupus-like disease (Sun et al 2013), traumatic brain injury (Krämer et al 2022), and myocardial infarction (Cabrera-Fuentes et al 2014). In humans, sterile inflammation causing cell death and the release of RNPs into the extracellular space seems to be an important trigger of Systemic Lupus Erythematosus (Dou et al 2024). In addition, polytrauma induces exRNA release followed by TLR7-dependent systemic inflammation in mice (Suen et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, several RNA species are stable in the extracellular space even when not associated with EVs. These resilient extracellular RNAs include ribonucleoprotein particles (RNPs) such as Ago2/miRNA complexes (Turchinovich et al 2011; Arroyo et al 2011; Geekiyanage et al 2020), and protein-protected RNA fragments (LaPlante et al 2023) derived from the ribosome (Tosar et al 2020, 2022; Costa et al 2023), U2 snRNPs (Tosar et al 2022), and possibly Xist RNPs (Dou et al 2024). Additionally, a population of intrinsically stable nicked tRNAs circulates in human biofluids, probably unprotected or naked (Costa et al 2023).…”
Section: Discussionmentioning
confidence: 99%